Reduction of income inequality and subjective well-being in Europe - Tamás Hajdu; Gábor Hajdu (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
Using four waves of the European Social Survey (179,273 individuals from 29 countries) the authors analyze the association of reduction of income inequality by governmental taxes and transfers (redistribution) with subjective well-being. Their results provide evidence that people in Europe are negatively affected by income inequality, whereas reduction of inequality has a positive effect on well-being. Since the authors simultaneously estimate the effects of income inequality and its reduction, their results might indicate that not only the outcome (inequality), but also the procedure (redistribution) that leads to the outcome influences subjective well-being. Their results also show that the positive effect of redistribution is stronger for less affluent members of the society and left-wing oriented individuals. While post-government inequality seems to have no significant effect in Western Europe, its impact is negative and highly significant in Eastern Europe.
Keywords: D63; I31; 330; Subjective well-being; satisfaction; inequality; redistribution; inequality reduction